Green Accounting dan Kinerja Bisnis: Peranan Proper sebagai Pemoderasi - Muljono, Michael; Dyna Rachmawati (Universitas Kristen Krida Wacana, 2024)
The aim of this research is to examine the effect of green accounting on business performance with PROPER as a moderator. The object of this research is the manufacturing industry on the IDX for the 2019-2021 period. We use two measures for green accounting, they are indices and ratios. Business performance is measured by ROA. PROPER is measured using dummy variables. The data analysis technique used is MRA. The results of this research prove that green accounting as proxied by an index (ratio) has a positive effect (no effect) on business performance. PROPER has a partial moderating role in the green accounting index on ROA relationship. However, PROPER does not have a moderating role in the relationship between ratio and ROA. The implication of the results of this research is that companies that follow PROPER tend to have implemented green accounting so that they are able to maintain their sustainability. This research found several findings related to public information, first, environmental costs. Not many companies disclose environmental costs in their sustainability reports. Second, several companies provided information that they had participated in PROPER, but were not on the list of PROPER participants issued by the Ministry of the Environment. Keywords: business performance, green accounting, index GA, PROPER, ratio GA